Multiple Pickering emulsions stabilized by the same particles with different extent of hydrophobization in situ - Zhu, Yue; Chen, Tingting; Cui, Zhenggang (Frontiers in Chemistry, 2022)
Multiple emulsions are widely used in pharmaceuticals, foods, and cosmetics. However, those stabilized by surfactants with different HLB values are generally unstable due to the diffusion of the surfactants between inner and outer interfaces. Here, we report that multiple W/O/W emulsions can be prepared by using the same particles in combination with a surfactant of different concentrations. The less surface-active raw CaCO3 nanoparticles can be hydrophobized to surface-active in situ by adsorption of the anionic surfactant SDS, and the wettability of the particles can be controlled to be suitable for stabilizing both O/W and W/O Pickering emulsions by adjusting the surfactant concentration. With toluene as oil phase, the CaCO3 particles at 1.0 wt% tend to stabilize a W/O emulsion in the presence of 3 mm SDS in an aqueous solution, which can then be further dispersed in an aqueous phase with 1.0 wt% CaCO3 and SDS below 1 mm to form a W/O/W multiple emulsion. The effects of the ratio of W/O emulsion to the outer water phase and the preparation methods on stabilization of multiple emulsions were examined. With a ratio smaller than 3:1 and by gentle magnetic stirring, the multiple emulsions obtained can stay stable for at least a month without coalescence. This simple method not only ensures stabilization of multiple emulsions but also avoids complicated synthesis of colloid particles with different wettability.